Assessment of oil palm smallholders{u2019} adoption of roundtable on sustainable palm oil practices in Thailand - Wipadsara Rodthong; Datta, Avushek; Kuwornu, John K. M.; Anal, Anil Kumar; Tsusaka, Takuji W.; Ministry of Agriculture and Cooperatives (MOAC), Thailand; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
The increased demand for palm oil and the processed extract from fresh fruit bunches leads to a rapid expansion of oil palm plantations in tropical Southeast Asian countries. The success of the oil palm industry has been attributed to a substantially higher oil yield per hectare compared with other oilseed crops. However, the increase in oil palm production has negatively impacted biodiversity, led to conflicts over land use, and contributed to soil and environmental degradation in various areas. The Roundtable on Sustainable Palm Oil (RSPO) was formed in 2004 in response to adverse environmental impacts caused by the expansion of oil palm production. It created voluntary standards to accelerate adoption of improved practices along the supply chain to ensure environmental benefits. However, the rate of adoption among smallholders of the practices RSPO recommends remains low. This study assessed smallholder farmers{u201F} perceptions regarding the adoption of RSPO practices, the factors influencing smallholder farmers{u201F} adoption decisions, and the intensity of adoption using primary data obtained from 723 randomly selected oil palm producers in the southern region of Thailand, of which 333 RSPO were adopters and 390 were non-adopters. The results of the weighted average index analysis revealed that there were different perceptions regarding the RSPO practices between the two farmer groups (adopters and non-adopters). The adopters were more positive about the RSPO practices than the non-adopters. The reason for adoption of RSPO practices was the Thai government{u201F}s provision of financial support for RSPO-related operations for adopters, whereas most non-adopters expected further provision by the government. Although record keeping was a key barrier for adopters{u201F} obtaining the required certification, they would like to continually adopt the RSPO practices in the future because of the expectation to receive premium prices for selling certified oil palm. The results of the binary logit and two-limit Tobit regressions revealed that total farm labor, farm size, number of training sessions attended, access to information, extension services, support services, and perceived ease of adoption of the practices had positive effects on the intensity of adoption. However, the age of oil palm trees negatively influenced the intensity of adoption. The continuous and intensified role of the government and institutions are critical for the adoption of the RSPO practices. It is important to strengthen capacity building activities and extension/support services to enhance the adoption of the RSPO practices among small-scale farmers{u201F} in Thailand.
A Dissertation submitted in partial fulfillment of the requirements for the Degree of Doctor of Philosophy in AgriBusiness Management
Thesis (Ph.D.) - Asian Institute of Technology, 2020
Keywords: Palm oil industry -- Government policy -- Thailand; Farms, Small -- Government policy -- Thailand